2021
DOI: 10.3390/vaccines9111287
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Double Mosaic Virus-like Particle-Based Vaccine against SARS-CoV-2 Incorporates Both Receptor Binding Motif (RBM) and Fusion Domain

Abstract: COVID-19 has emerged, and has rapidly become a major health problem worldwide, causing millions of mortalities. Vaccination against COVID-19 is the most efficient way to stop the pandemic. The goal of vaccines is to induce neutralizing antibodies against SARS-CoV-2 virus. Here, we present a novel double mosaic virus-like particle (VLP) displaying two independent neutralizing epitopes, namely the receptor binding motif (RBM) located in S1 and the fusion peptide (AA 817–855) located in S2. CuMVTT virus-like part… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Similar results were obtained with RBM fused to VLP AP205 [33]. In addition, we generated a double mosaic particle, which induced neutralizing antibodies against both RBM in S1 as well as the cleavage site in S2, a second, "minor" neutralizing epitope [34].…”
Section: Examples Of Commonly Usedsupporting
confidence: 77%
“…Similar results were obtained with RBM fused to VLP AP205 [33]. In addition, we generated a double mosaic particle, which induced neutralizing antibodies against both RBM in S1 as well as the cleavage site in S2, a second, "minor" neutralizing epitope [34].…”
Section: Examples Of Commonly Usedsupporting
confidence: 77%
“…Moreover, as it was expected for the SARS-CoV-2 vaccine, in both with and without adjuvant conditions, the IgG titer was normally higher four weeks after injection than two weeks later. Similarly, mice immunization and IgG evaluation through a VLP-based developed vaccine for SARS-CoV-2 based on S1 and S2 epitopes showed that signi cant anti-spike IgG antibody was produced 28 days after the immunization program, during which two doses of vaccine were administered on days on 0 and 21 [47].…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, as expected for the SARS-CoV-2 vaccine, in both with and without adjuvant conditions, the IgG titer was normally higher 4 weeks after injection than 2 weeks later. Similarly, mice immunization and IgG evaluation through a VLP-based developed vaccine for SARS-CoV-2 based on S1 and S2 epitopes showed that a significant amount of anti-spike IgG antibody was produced 28 days after the immunization program, during which two doses of vaccine were administered on days 0 and 21 [ 47 ]. Although the humoral immunity results indicate the immunoactivity of the recombinant protein vaccine and confirm its successful expression, introducing this antigenic protein as an efficient vaccine needs comprehensive cellular immunity evaluations.…”
Section: Discussionmentioning
confidence: 99%